2015
DOI: 10.1002/2015jd023137
|View full text |Cite
|
Sign up to set email alerts
|

Modeling 2 m air temperatures over mountain glaciers: Exploring the influence of katabatic cooling and external warming

Abstract: Air temperature is one of the most relevant input variables for snow and ice melt calculations.However, local meteorological conditions, complex topography, and logistical concerns in glacierized regions make the measuring and modeling of air temperature a difficult task. In this study, we investigate the spatial distribution of 2 m air temperature over mountain glaciers and propose a modification to an existing model to improve its representation. Spatially distributed meteorological data from Haut Glacier d'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(131 citation statements)
references
References 50 publications
11
120
0
Order By: Relevance
“…During daytime, turbulent mixing of the glacier boundary layer with the up-valley anabatic winds may erode the shallow katabatic layer of a small glacier (Ayala et al, 2015), and glacier boundary layer temperatures have been found to be higher than expected (Carturan et al, 2015). This effect is exacerbated by solar heating of the unglaciated terrain surrounding the glacier, which causes instability in the overlying boundary layer.…”
Section: Distributing Model Input Variables Over the Glacier Surfacementioning
confidence: 93%
See 2 more Smart Citations
“…During daytime, turbulent mixing of the glacier boundary layer with the up-valley anabatic winds may erode the shallow katabatic layer of a small glacier (Ayala et al, 2015), and glacier boundary layer temperatures have been found to be higher than expected (Carturan et al, 2015). This effect is exacerbated by solar heating of the unglaciated terrain surrounding the glacier, which causes instability in the overlying boundary layer.…”
Section: Distributing Model Input Variables Over the Glacier Surfacementioning
confidence: 93%
“…1). The limited aerial and vertical extent of the modern glacier favours the steep vertical air temperature gradient along the glacier surface, but on larger glaciers such as LG during its L19 extent, the air temperature gradient over the glacier surface is strongly modified by the katabatic wind field (Ayala et al, 2015;Greuell and Böhm, 1998;Shea and Moore, 2010); and the influence of long-wave emissions from surrounding terrain is drastically reduced as the glacier fills the cirque (Fig. 1).…”
Section: The Impact Of Glacier Extent On the Proxy Potential Of Lewismentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, a prevailing up-glacier wind was recognized, but it cannot be attributed unequivocally to valley winds because the direction roughly corresponds to prevailing synoptic winds in the Ortles-Cevedale area (Gabrieli et al, 2011). The occurrence of weaker local winds and more relevant entrainment of synoptic winds have been hypothesized, for example, by Ayala et al (2015), for glaciers without a well-defined tongue. On the other hand, although katabatic flows were generally absent, this site was the coldest in summer 2011, exhibiting a mean depression of 1 • C compared to the ambient temperature (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…During the day the LR has two cycles with minima in magnitude close to −0.005 • C m −1 at 11:00 and −0.004 • C m −1 at 19:00, separated by a maximum of −0.007 • C m −1 at 16:00. While the LR minima are likely to be related to the strengthening of katabatic flow during daytime (Petersen and Pellicciotti, 2011), the afternoon maximum is potentially caused by the erosion of the katabatic boundary layer on the lower glacier tongue, due to warm air advection from bare rock surfaces at the glacier sides and proglacial area (van de Broeke, 1997;Ayala et al, 2015). Using the hourly LR, we distribute air temperatures over the entire glacier surface on a 30 m grid at an hourly time step, using the ASTER GDEM V2 and the glacier outline which was digitized from an ASTER image of 27 March 2010.…”
Section: Distributed Degree-hour Model (Ddhm)mentioning
confidence: 99%